Mapping yield and yield-related traits using diverse common bean germplasm - Reinprecht, Yarmilla; Schram, Lyndsay; Perry, Gregory E.; Morneau, Emily; Smith, Thomas H.; Pauls, K. Peter (Frontiers in Genetics, 2024)
Common bean (bean) is one of the most important legume crops and mapping genes for yield and yield-related traits is essential for its improvement. However, yield is a complex trait that is typically controlled by many loci in crop genomes. The objective of this research was to identify regions in the bean genome associated with yield and a number of yield-related traits using a collection of 121 diverse bean genotypes with different yields. The beans were evaluated in replicated trials at two locations, over two years. Significant variation among genotypes was identified for all traits analyzed in the four environments. The collection was genotyped with the BARCBean6K_3 chip (5,398 SNPs), two yield/antiyield gene-based markers and seven markers previously associated with resistance to common bacterial blight (CBB), including a Niemann-Pick gene-based (NPP) marker. Over 90% of the SNPs were polymorphic and separated the panel into two main groups of small-seeded and large-seeded beans, reflecting their Mesoamerican and Andean origins. Thirty-nine significant marker-trait associations (MTAs) were identified between 31 SNPs and 15 analyzed traits on all 11 bean chromosomes. Some of these MTAs confirmed genome regions previously associated with the yield and yield-related traits in bean, but a number of associations were not reported previously especially those with derived traits. Over 600 candidate genes with different functional annotations were identified for analyzed traits in the 200 Kb centered on significant SNPs. Fourteen SNPs were identified within the gene model sequences and five additional SNPs significantly associated with five different traits were located less than 0.6 Kb from the candidate genes. The work confirmed associations between two yield/anti-yield gene-based markers, (AYD1m and AYD2m) on chromosome Pv09, with yield and identified their association with a number of yield-related traits, including seed weight. The results also confirmed the usefulness of the NPP marker in screening for CBB resistance. Since disease resistance and yield measurements are environmentally dependent and labor intensive, the three gene-based markers (CBB- and two yield-related) and QTL that were validated in this work may be useful tools for simplifying and accelerating the selection of high yielding and CBB resistant bean cultivars.